Efficacy of some local isolates of Beauveria bassiana(Bals.) and Metarhizium anisopliae (Met.) in control of mosquito larvae of Culex quinquefasciatus (Say) (Baghdad Science Journal, 2015)
The main aim of this study is to investigate the ability of four local entomopathogenic isolates Beauveria bassiana (Bals.) and Metarhizium anisopliae (Met.) to control the mosquito larvae in the lab. The results revealed that the isolate (MARD48) B .bassiana reduced the survival rate of the mosquito larvae to (80%) followed by the isolate M. anisopliae (MARD10) to (90%) in the first two days of treatment, and 60 and 66% respectively in the third day. The results also showed that the isolate B. bassiana (MARD48) killed 50% of the population (LC50) with the concentration 1×104 conidia/ml compared to 1×107 conidia/ml for the isolates B. bassiana (MARD14) and M. anisopliae (MARD10), and 1×108 conidia/ml for the isolate B .bassiana (MARD76). The shortest lethal time was at concentration 1×107 conidia/ml within 3.3 day for the isolate B. bassiana (MARD48); while, it was 2.3 day for the isolate M. anisopliae (MARD10) of the concentration of 6 1×1011 spores / ml . According to the results, the isolate B. bassiana (MARD48) revealed the lowest concentration killed 50% (LC50) of the population and shortest time.